The Influence of Principal Leadership, School Culture, and Technology Use on Elementary School Teacher Performance in Batu Ampar District - Marusaha MP Siahaan; Nurtanio Agus Purwanto (STKIP Singkawang, 2025)
This research aims to determine the effect of school principal leadership on teacher performance, the influence of school culture on teacher performance, the influence of technology utilization on teacher performance, and the simultaneous influence of school principal leadership, school culture, and technology utilization on the performance of elementary school teachers in Batu Ampar District. This research is a quantitative study using a survey method. The population of this study consists of 223 elementary school teachers in Batu Ampar District, Batam City, Riau, Indonesia. The sample size was determined using the Stratified Random Sampling method with Slovin’s formula. Data collection was conducted using questionnaires distributed to all samples. Data were analyzed using descriptive analysis, correlation, and regression analysis using IBM SPSS Statistic version 27. The results of the study indicate that: 1) school principal leadership has a positive and significant effect on the performance of elementary school teachers in Batu Ampar District, 2) school culture has a positive and significant effect on the performance of elementary school teachers in Batu Ampar District, 3) technology utilization has a positive and significant effect on the performance of elementary school teachers in Batu Ampar District, and 4) school principal leadership, school culture, and technology utilization simultaneously have a positive and significant effect on the performance of elementary school teachers in Batu Ampar DistrictThis research aims to determine the effect of school principal leadership on teacher performance, the influence of school culture on teacher performance, the influence of technology utilization on teacher performance, and the simultaneous influence of school principal leadership, school culture, and technology utilization on the performance of elementary school teachers in Batu Ampar District.This research is a quantitative study using a survey method. The population of this study consists of 223 elementary school teachers in Batu Ampar District, Batam City, Riau, Indonesia. The sample size was determined using the Stratified Random Sampling method with Slovin’s formula. Data collection was conducted using questionnaires distributed to all samples. Data were analyzed using descriptive analysis, correlation, and regression analysis using IBM SPSS Statistic version 27. The results of the study indicate that: 1) school principal leadership has a positive and significant effect on the performance of elementary school teachers in Batu Ampar District, 2) school culture has a positive and significant effect on the performance of elementary school teachers in Batu Ampar District, 3) technology utilization has a positive and significant effect on the performance of elementary school teachers in Batu Ampar District, and 4) school principal leadership, school culture, and technology utilization simultaneously have a positive and significant effect on the performance of elementary school teachers in Batu Ampar District